Partitioning assimilatory nitrogen uptake in streams: an analysis of stable isotope tracer additions across continents. Issue 1 (1st December 2017) - Tank, J. L.; Martí, E.; Riis, T.; von Schiller, D.; Reisinger, A. J.; Dodds, W. K.; Whiles, M. R.; Ashkenas, L. R.; Bowden, W. B.; Collins, S. M.; Crenshaw, C. L.; Crowl, T. A.; et al.
Abstract: Headwater streams remove, transform, and store inorganic nitrogen (N) delivered from surrounding watersheds, but excessive N inputs from human activity can saturate removal capacity. Most research has focused on quantifying N removal from the water column over short periods and in individual reaches, and these ecosystem‐scale measurements suggest that assimilatory N uptake accounts for most N removal. However, cross‐system comparisons addressing the relative role of particular biota responsible for incorporating inorganic N into biomass are lacking. Here we assess the importance of different primary uptake compartments on reach‐scale ammonium (NH4 + ‐N) uptake and storage across a wide range of streams varying in abundance of biota and local environmental factors. We analyzed data from 17 15 N‐NH4 + tracer addition experiments globally, and found that assimilatory N uptake by autotrophic compartments (i.e., epilithic biofilm, filamentous algae, bryophytes/macrophytes) was higher but more variable than for heterotrophic microorganisms colonizing detrital organic matter (i.e., leaves, small wood, and fine particles). Autotrophic compartments played a disproportionate role in N uptake relative to their biomass, although uptake rates were similar when we rescaled heterotrophic assimilatory N uptake associated only with live microbial biomass. Assimilatory NH4 + ‐N uptake, either estimated as removal from the water column or from the sum uptake of all individual compartments, was four times higher in open‐ than in closed‐canopy streams. Using Bayesian Model Averaging, we found that canopy cover and gross primary production (GPP) controlled autotrophic assimilatory N uptake while ecosystem respiration (ER) was more important for the heterotrophic contribution. The ratio of autotrophic to heterotrophic N storage was positively correlated with metabolism (GPP: ER), which was also higher in open‐ than in closed‐canopy streams. Our analysis shows riparian canopy cover influences the relative abundance of different biotic uptake compartments and thus GPP:ER. As such, the simple categorical variable of canopy cover explained differences in assimilatory N uptake among streams at the reach scale, as well as the relative roles of autotrophs and heterotrophs in N storage. Finally, this synthesis links cumulative N uptake by stream biota to reach‐scale N demand and provides a mechanistic and predictive framework for estimating and modeling N cycling in other streams.